The Potential of RIP (Ribosome Inactivating Protein) as Biopesticides - Tati Suharti; Dharmawati F Djam’an (Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Makassar, 2019)
RIP (Ribosome Inactivating Protein) produced by plants that can act as a plant defense from pest and disease. This protein is widely used as an anti-fungal, anti-bacterial, anti-virus and anti-insect. Therefore, RIP contained in plants has the potential to be used for environmentally friendly biopesticides. The purpose of this paper is to provide information on RIP derived from plants and its potential as a biopesticide.The mode of action of RIP works is by inhibiting protein synthesis during translating process of pest and plant pathogen. RIP has a broad spectrum so that it can overcome insect pests from various orders and pathogens both fungi, bacteria and viruses. Some types of plants that contain RIP include neem, ginger, turmeric, galangal, castor bean, jatropha, soursop and bitter melon. RP applications can be in the form of oil, essential oils, solutions, flour, ash and simplicia. RIP can be applied to seeds, seeds, plants and post-harvest products. The advantages of using RIP include easily available materials, inexpensive, easy to application and environmentally friendly.The plants contain RP has high potency to commercially developed so in the future, the controlling of pest and disease rely on the plants contain RIP both direct and in the pesticides formulations form. Therefore echo friendly plantation programme can be realized.